Informality, Trade Policies and Smuggling in West Africa - Benjamin, Nancy; Golub, Stephen; Mbaye, Ahmadou Aly (Taylor and Francis, 2015)
In West Africa, recorded intra-regional trade is small but informal cross-border trade (ICBT) is pervasive, despite regional integration schemes intended to promote official trade. We argue that ICBT must be understood in light of two features of West African national boundaries: divergent economic policies between neighboring countries and the ease with which informal operators can ship goods across borders. We focus on two ICBT clusters: Senegal–The Gambia and Nigeria–Benin–Togo. Nigeria and Senegal have protected their domestic industries with high import barriers, whereas Benin, Togo and The Gambia have maintained lower import taxation. These differential trade policies, together with high mobility of goods and people across borders, lead to widespread smuggling, with goods imported legally in low-tax countries and re-exported unofficially to countries with higher import duties.